Sicherheit und Differenz in historischer Perspektive | Security and Difference in Historical Perspective - Ruby, Sigrid; Krause, Anja (2022)
The contributions in this book examine historical and current conceptions of security, i.e. discourses and practices aimed at collective security, with regard to their interrelationship with categories of diversity such as gender, race, status, religion, etc. and how and where they intersect. What does a historical perspective contribute to an intersectional critique of security studies? Multidisciplinary and using diverse empirical research subjects from the Middle Ages to the present, the book analyses the perception, significance and effects of practices and discourses relevant to security. It will appeal to experts engaged in historical and social science (security) research, but also to a broader readership interested in security and diversity.